PEMIKIRAN IBNU KHALDUN TENTANG KETENAGAKERJAAN DAN RELEVANSINYA DI INDONESIA - Darsi Ahmadan (Program Studi Perbankan Syariah, 2022)
Ibn Khaldun's thoughts on employment and its relevance in Indonesia???, with the background of the problem, namely, the enactment of Law Number 13 of 2003, is part of the government's grand scenario to organize and negotiate common interests between employers, workers and the government. If companies have an interest in capital development, workers have an interest in increasing income, then the government secures the macro economy. Because without conducive conditions, the economy of a country will be shaken. Ibn Khaldun was a Muslim scientist who had many thoughts in various fields such as economics. In his economic sub-study on employment, which is contained in Muqadimah's book on the theory of value, division of labor and international trade, the law of supply and demand, consumption, production, money, trade cycles, public finance, and several macroeconomic discussions. The type of research is library research. The type of data used is primary data, namely all of Ibn Khaldun's works that discuss employment, both implied and explicit, as well as data on employment in Indonesia. While secondary data is related to formal objects and enrichment that discusses employment in Indonesia. From the results of the researcher's analysis, it is known that, firstly, Ibn Khaldun's rationale for the emergence of the employment system because, to meet basic personal (dharuri), secondary (hajiyyah) and tertiary (tahsinat) needs, as well as to meet the needs of many people (subjective mass), is called